(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The integration of Artificial Intelligence (AI) and Internet of Things (IoT) technologies has revolutionized agricultural practices, particularly in vertical irrigation systems. This paper explores the application of AI-powered IoT devices to optimize water usage, enhance crop yield, and reduce operational costs in vertical farming. By leveraging real-time data analytics, machine learning algorithms, and automated control systems, these technologies enable precise irrigation management. The study presents a methodology for implementing such systems, analyzes their performance through empirical data, and discusses their implications for sustainable agriculture. Results indicate significant improvements in water efficiency and crop productivity, with potential scalability across diverse farming environments.